An assessment on inflation risk and its effects on business operations - Hacıoğlu, Ümit; Dinçer, Hasan; Parlak, Burcu (IGI Global, 2015)
The latest economic crisis in the world affected business operations and decision making process at management rank. One of the major components of financial system is business organizations within the financial environment, which injects cash to the system and individuals. Therefore, fluctuations in financial system regarding inflationary trends should be evaluated and risk management functions for banking operations should be facilitated. In this chapter, operating mechanism of financial system, risks, inflation and the effects of inflation on business operations have been outlined from a theoretical perspective.
Keywords: Assessment; Inflation; Business Operations